The Effect of Hypertrophy Exercises in Free Weights - Special Instruments in the Maximum Strength and Muscle Size of Advanced Bodybuilders - Mutshr, Ali (Journal of Physical Education, 2019)
The Effect of Hypertrophy Exercises in Free Weights - Special Instruments in the Maximum Strength and Muscle Size of Advanced Bodybuilders The study aimed at identifying the effect of hypertrophy exercises with free weights and hypertrophy exercises with special devices and its effect on maximum strength and muscle size of bodybuilders. The researcher used the experimental method to suit the nature of the problem. The study was conducted on a sample of 16 players divided into two equal groups. The first experimental group carried out free weight training, while the second experimental group trained using special equipment. The two groups were subjected to a pre-test and a post-test maximum strength power and body girths. The training program lasted for (8) weeks with (3) training sessions per week. The data was collected and treated suing proper statistical operations to conclude that there were no significant statistical differences in both experimental groups in maximum strength and muscle size. Finally the researcher recommended that the use of hypertrophy training in training modules for bodybuilding players should be used for its positive effect on the development of maximum strength and increasing muscular size.